Genotypic differences in photosynthesis and its associated parameters in relation to yield among barnyard millet (Echinochloa frumentacea) ,genotypes under rainfed condition in hills - KUMAR, PRAMOD; LAKSHMI, N JOYTHI; DUBE, S D; MANI, V P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment with twelve genotypes of barnyard millet (Echinochloa frumentacea (Roxb.) Link) was conducted during 1997-98 under rain fed condition in hills to understand the photosynthetic basis of yield. A significant genotypic vuriations in rates of photosynthesis and its associated parameters was recorded during vegetative and reproductive phases. Mean rates of leaf photosynthesis, canopy photosynthesis, trainspiration, stomatal conductance, leaf temperature depression and total dry-matter had significant positive association with grain yield, whereas the association of plant height, harvest index and test weight with yield was not significant. Mean photosynthesis rate showed positive association with harvest index and test weight. Tiller number/plant had poor negative association with grain yield.